I. Nékrosius, V. Nékrosius, S. Vélyvis, Romènu teisé, 1999 - Pikulska-Robaszkiewicz, Anna (Czasopismo Prawno-Historyczne, 2001)
Recenzja: I. Nekrošius, V. Nekrošius, S. V lyvis, Romėnų teis , Vilnius 1999, ss. 263, (Wydawnictwo Justitia).